Extended exergy analysis of a solar driven water production plant via reverse osmosis. (25th July 2021) - Ünal, Canberk; Açıkkalp, Emin; Borge-Diez, David; Hepbasli, Arif
Graphical abstract: Highlights: Novel small scale solar desalination plant provides a solution for water scarcity. Proposed desalination plant using solar energy studied via extended exergy analysis. Extended exergy analysis evaluates solar plant performance and sustainability. Labor and capital exergy equivalents are 42.68 MJ/workhour and 12.09 MJ/Euro. Products having much higher specific exergy content could be produced. Abstract: Water scarcity and contamination of available water are becoming one of the most complex problems worldwide and they compromise economic development, global sustainability, and human supply, among others. Water is required in almost all human activities and also for planet equilibrium in terms of biodiversity. In this research a new home scaled water desalination plant, using a reverse osmosis technology and driven with solar energy is analyzed via extended exergy analysis, which is one of the most accurate methods for evaluating both energy performance and sustainability. The proposed system, that is presented and analyzed, consists of a solar concentrator having 1000 concentrating rate, a Photon Enhanced Thermionic Emitter, a Dye-Sensitized Solar Cell for the electricity generation and a Reverse Osmosis Desalination Plant (RODP) for water purification using the produced electricity. This system allows water desalination in small scale plants requiring low density energy sources and can produce sustainable water for multiples uses, such as domestic use or agricultural, among others. The most important results are labor and capital exergy equivalents, 42.68  MJ/workhour and 12.09  MJ/Euro, respectively, and an exergy destruction of 389.700 GJ for all the system annually. The proposed technology can be extended and used in different locations and the Extended Exergy Analysis can be used as a powerful tool for both design and optimization.